PENGELOMPOKKAN KABUPATEN DI PROVINSI JAWA TENGAH BERDASARKAN KARAKTERISTIK IKLIM MENGGUNAKAN FUZZY CLUSTERING - NOVENRODUMETASA, NATALIE; GANDHIADI, G. K.; JAYANEGARA, KETUT (E-Jurnal Matematika; Vol 13 No 1 (2024), 2024)
There are many factors affecting human life, one of which is climate. Differences in climatic conditions in each region result in differences in the environment in society. The differences are referred to as potential natural resources, livelihoods, and social cultural conditions. The climate has an impact on culture in terms of how people dress, the shape of houses, and so on. The regency group in Central Java Province is based on similarities in climate characteristics using fuzzy clustering. The data used were taken from Central Java Provincial Statistical Office in 2022.The results of district grouping in Central Java Province are based on similarities in climate characteristics using fuzzy clustering with 4 different number of clusters and the validity tests of the Partition Coefficient and Classification Entropy indices. Based on the results of the index validity test, the optimal grouping results are 2 clusters with a Partition Coefficient value of 0.911233 and a Classification Entropy value of 0.07979. The 1st cluster consists of 13 districts with a cluster center at 27.9°C for air temperature, 2418mm for rainfall, and 804% for keelThe 2nd cluster and airbase consist of 22 cluster central districts at 26.6 °C for air temperature, 4087 mm for rainfall, and 81.3% for humidity.